Mortality rates due to amyotrophic lateral sclerosis in São Paulo City from 2002 to 2006 - Sheila Evangelista de Matos; Mônica Tilli Reis Pessoa Conde; Francis Meire Fávero; Mauro Taniguchi; Abrahão Augusto Juviniano Quadros; Sissy Veloso Fontes; Acary Souza Bulle Oliveira (Arquivos de Neuro-Psiquiatria, 2011)
OBJECTIVE: To describe the mortality rates of amyotrophic lateral sclerosis (ALS) in the city of São Paulo as a function of demographics, year, and region. METHOD: This was a retrospective descriptive study. Information was obtained from death certificates registered at the Program for the Improvement of Mortality Information, Municipal Health Department (PRO-AIM/SMS), coded as G12.2 according to International Classification of Diseases (ICD-10), from 2002 to 2006. RESULTS: Over the studied time, were found 326 deaths (51.6% women, overall mean age of 64.1 years). Highest deaths percentages happened in those from 60 to 69 and 70 to 79 years and in white individuals. ALS mortality rates ranged 0.44/100,000 in 2002 and 0.76/100,000 in 2006. No significant changes overtime in administrative districts were found. CONCLUSION: ALS mortality rates in São Paulo were lower in comparison to other countries, however any risk factor in our environment, lifestyle or genetic characteristics were found.